Aberrant insulin signaling in Alzheimer's disease: current knowledge - Bedse, Gaurav; Di Domenico, Fabio; Serviddio, Gaetano; Cassano, Tommaso (Frontiers in Neuroscience, 2015)
Alzheimer’s disease (AD) is the most common form of dementia affecting elderly people. AD is a multifaceted pathology characterized by accumulation of extracellular neuritic plaques, intracellular neurofibrillary tangles (NFTs) and neuronal loss mainly in the cortex and hippocampus. AD etiology appears to be linked to a multitude of mechanisms that have not been yet completely elucidated. For long time, it was considered that insulin signaling has only peripheral actions but now it is widely accepted that insulin has neuromodulatory actions in the brain. Insulin signaling is involved in numerous brain functions including cognition and memory that are impaired in AD. Recent studies suggest that AD may be linked to brain insulin resistance and patients with diabetes have an increased risk of developing AD compared to healthy individuals. Indeed insulin resistance, increased inflammation and impaired metabolism are key pathological features of both AD and diabetes. However, the precise mechanisms involved in the development of AD in patients with diabetes are not yet fully understood. In this review we will discuss the role played by aberrant brain insulin signaling in AD. In detail, we will focus on the role of insulin signaling in the deposition of neuritic plaques and intracellular NFTs. Considering that insulin mitigates beta-amyloid deposition and phosphorylation of tau, pharmacological strategies restoring brain insulin signaling, such as intranasal delivery of insulin, could have significant therapeutic potential in AD treatment.